Efektivitas Permainan Edukatif Berbasis Canva dalam Meningkatkan Hasil Belajar Ilmu Pengetahuan Alam dan Sosial Siswa Sekolah Dasar - Kusmirah; Siti Dewi Maharani; Sardianto Markos Siahaan (Postgraduate, University of Mataram, 2025)
This study aims to develop a Canva-based educational game entitled “How Breathing Helps Me in Daily Activities” as an innovative learning medium for Ilmu Pengetahuan Alam dan Sosial (IPAS) in elementary schools. The research employed a Research and Development (R&D) approach consisting of four stages: analysis, design, development, and limited trials. The product was developed using the Canva platform and incorporates interactive game elements to support students’ engagement with the topic of the human respiratory system. Validation was conducted by material, media, and language experts, while practicality was examined through individual and small-group trials involving students. Learning improvement was analyzed using a one-group pretest–posttest design. The validation results indicated that the developed educational game achieved a very valid category in terms of content accuracy, media design, and language clarity. Practicality testing yielded a score above 90%, indicating that the media is easy to use, engaging, and appropriate for the cognitive characteristics of elementary school students. The analysis of learning outcomes showed an increase in students’ average scores from 50,40 in the pretest to 87,13 in the posttest, with an N-gain value of 0.74 categorized as high. These findings suggest that the developed game supports students’ understanding of the human respiratory system and its relationship to daily activities. Overall, this study contributes empirical evidence that a Canva-based educational game on the theme “How Breathing Helps Me in Daily Activities” is valid, practical, and demonstrates promising learning outcomes for IPAS instruction at the elementary level. Further studies using experimental designs with control groups are recommended to strengthen evidence of its effectiveness and generalizability.